Nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nano composite material as well as preparation method and application of nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nano composite material

By using nitrogen hybrid honeycomb carbon load Feooh/Fenico-LDH heterogeneous structure nano-composite materials in the oxygen catalyst, it solves the problem of poor conductivity and complicated preparation process of existing electrocatalysts, and achieves high activity and high stability. Preparation with low -cost catalysts is suitable for applications in the field of energy and environment.

CN119332285AActive Publication Date: 2025-01-21TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411278618.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-21
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing oxygen precipitation reaction electrocatalysts have problems such as poor conductivity, easy agglomeration and stacking, and masking of active sites, which limit their electrocatalytic activity and stability. The traditional preparation methods are complex and difficult to adapt to industrial-scale production.

Method used

The nitrogen hybrid honeycomb carbon load is feed, the heterogeneous structure of the heterogeneous structure of the heterogeneous structure, and simplify the preparation process through a template-free high-temperature carbonization strategy, and uses non-precious metal front-drives and organic small molecules to obtain high activity and high stability catalysts.

Benefits of technology

The significant improvement of catalytic activity and stability has been realized. The process is simple and low in cost. It is suitable for medium -sized industrialized production and has a broad application prospects in the field of energy and environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332285A_ABST
    Figure CN119332285A_ABST
Patent Text Reader

Abstract

The invention provides a nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nano composite material as well as a preparation method and application thereof, and belongs to the field of nano composite materials. The preparation method is characterized by comprising the following steps that organic salt and nitrogen-containing micromolecules are completely dissolved in a solvent, nitrogen-hybridized honeycomb carbon is obtained through heating evaporation, high-temperature calcination and acid liquor etching, the obtained nitrogen-hybridized honeycomb carbon and a metal cobalt precursor are evenly mixed in the solvent, and the nitrogen-hybridized honeycomb carbon / metal cobalt composite material is obtained. The preparation method comprises the following steps: adding an organic ligand to react to obtain metal organic framework / nitrogen-hybridized honeycomb carbon, uniformly mixing the obtained metal organic framework / nitrogen-hybridized honeycomb carbon, a metal nickel precursor and a metal iron precursor in a solvent to obtain a mixed solution, then transferring the mixed solution into a reaction kettle, and reacting to obtain the metal organic framework / nitrogen-hybridized honeycomb carbon / nickel-iron composite material which is excellent in performance, good in stability and low in cost. The FeOOH / FeNiCo-LDH heterostructure nanometer composite material has a typical honeycomb shape and is of a scaly FeOOH / FeNiCo-LDH heterostructure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanocomposite materials, and in particular relates to a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, a preparation method and application thereof. Background Art

[0002] In the face of the two major problems of energy shortage and environmental pollution, it is extremely important to develop a new energy system that is green, sustainable, low-cost and efficient. Hydrogen, as a clean energy carrier with high energy density, is believed to play an important role in the construction of new energy systems. Among them, water electrolysis hydrogen production technology, especially anion exchange membrane electrolysis water technology, has attracted great attention due to its environmental friendliness, green sustainability, safety and stability. The water electrolysis reaction consists of two half reactions: hydrogen evolution reaction and oxygen evolution reaction. As a key half reaction, the oxygen evolution reaction involves a complex multi-step proton-electron coupling process, has a slow kinetic process and a high overpotential, and is the key to affecting the efficiency of electrocatalytic water decomposition. Although precious metal-based catalysts such as RuO2 and IrO2 exhibit high catalytic activity, their high cost, scarcity and poor stability limit their further promotion, development and use in water electrolysis energy devices.

[0003] Transition metal layered double hydroxides TM-LDHs and porous carbon materials are widely used as electrocatalysts for oxygen evolution reaction due to their wide sources, low cost and easy preparation. However, TM-LDHs have problems such as poor conductivity, easy agglomeration and stacking, and masking of active sites, which seriously limit their intrinsic electrocatalytic activity. The effective composite of TM-LDHs and porous carbon can effectively improve the physicochemical properties such as the microenvironment of active sites and the surface energy of catalysts, thereby achieving a significant improvement in electrocatalytic activity and stability. However, the conventional hard template method or soft template method for preparing porous carbon often requires the introduction of additional template agents, such as silicon spheres, polystyrene spheres and mesoporous silicon, and then a series of tedious steps such as inverse casting, polymerization reaction, high-temperature pyrolysis, acid-base etching, etc., which is not conducive to industrial-scale production.

[0004] Therefore, designing an oxygen evolution reaction electrocatalyst with low cost, high performance, high durability and simple preparation process has become an urgent problem to be solved. Summary of the invention

[0005] The present invention is made to solve the above problems, and aims to provide a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, a preparation method and application thereof.

[0006] The invention provides a preparation method of a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, which has the following characteristics and comprises the following steps: step S1, completely dissolving an organic salt and a nitrogen-containing small molecule in a solvent, and subjecting the mixture to heating evaporation, high-temperature calcination and acid etching to obtain nitrogen-hybridized honeycomb carbon; step S2, uniformly mixing the nitrogen-hybridized honeycomb carbon and a metal cobalt precursor in a solvent, and then adding an organic ligand to react, and obtaining a metal organic framework / nitrogen-hybridized honeycomb carbon after the reaction; step S3, uniformly mixing the metal organic framework / nitrogen-hybridized honeycomb carbon, a metal nickel precursor and a metal iron precursor in a solvent to obtain a mixed solution, and transferring the mixed solution to a reactor to react under a preset temperature control program condition to obtain the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0007] The method for preparing the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention may also have the following characteristics: in step S1, the organic salt is any one or more of sodium gluconate, sodium acetate, ammonium citrate, potassium citrate, and sodium citrate; the nitrogen-containing small molecule is any one or more of aniline, alanine, glycine, urea, melamine, and hexamethylenetetramine; the solvent is any one or more of deionized water, methanol, ethanol, ether, N,N-dimethylacetamide, and N,N-dimethylformamide; and the molar ratio of the organic salt to the nitrogen-containing small molecule is 0.1 to 5.0.

[0008] The preparation method of the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention may also have the following characteristics: wherein, in step S1, when the heating evaporation process is performed, the heating method is an oil bath, a water bath or a sand bath, and the heating temperature is 50°C to 200°C; when the high-temperature calcination process is performed, the solid obtained by the heating evaporation process is directly placed in a tubular furnace for calcination without the need for additional template addition; the gas atmosphere is air, hydrogen, nitrogen or argon atmosphere, the temperature is 400°C to 1200°C, the heating rate is 2°C / min to 20°C / min, the calcination time is 0.5h to 8h; when the acid etching process is performed, the acid solution used for etching is hydrochloric acid, sulfuric acid or nitric acid, the acid concentration is 0.1M to 2M, the etching temperature is 20°C to 100°C, and the etching time is 10min to 120min.

[0009] The preparation method of the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention may also have the following characteristics: in step S2, the reaction temperature is 20°C to 100°C, the reaction time is 1h to 12h, the metal cobalt precursor is any one or more of cobalt oxalate, cobalt sulfate heptahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt acetate tetrahydrate, and cobalt acetylacetonate, the organic ligand is any one or more of 2-aminoterephthalic acid, imidazole, 2-methylimidazole, and 2-ethylimidazole terephthalic acid, and the solvent is any one or more of deionized water, methanol, ethanol, ether, N,N-dimethylacetamide, and N,N-dimethylformamide.

[0010] The method for preparing the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention may also have the following characteristics: in step S2, the amount of nitrogen-hybridized honeycomb carbon is 10 mg to 200 mg, the amount of metal precursor is 1-5 mmol, the amount of organic ligand is 0.5-50 mmol, the molar ratio of metal precursor to organic ligand is 0.1 to 2.0, and the amount of solvent is 10 mL to 200 mL.

[0011] The preparation method of the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention may also have the following characteristics: in step S3, the preset temperature control program conditions are set as follows: reaction temperature 20°C to 300°C, heating rate 1°C / min to 15°C / min, reaction time 2h to 20h, the metal nickel precursor is any one or more of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel oxalate, and nickel acetylacetonate, the metal iron precursor is any one or more of ferrous chloride tetrahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate, ferric acetate, anhydrous ferric chloride, ferric citrate, ferric acetate, and ferric acetylacetonate, and the solvent is any one or more of deionized water, methanol, ethanol ether, N,N-dimethylacetamide, and N,N-dimethylformamide.

[0012] The method for preparing the nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention may also have the following characteristics: in step S3, the amount of the metal organic framework / nitrogen-hybridized honeycomb carbon is 10 mg to 200 mg, the amount of the solvent is 10 mL to 200 mL, the amount of the metal nickel precursor is 0.5 to 3.0 mmol, and the amount of the metal iron precursor is 0.01 to 0.2 mmol.

[0013] The invention provides a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, which is characterized in that the nanocomposite material is prepared by the method for preparing the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the invention.

[0014] The present invention provides the use of any one of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite materials described above as an electrocatalyst.

[0015] Functions and Effects of the Invention

[0016] According to a nitrogen-hybridized honeycomb carbon negative FeOOH / FeNiCo-LDH heterostructure nanocomposite material, a preparation method and an application thereof provided by the present invention, in the preparation process of the nitrogen-hybridized honeycomb carbon negative FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention, in the first step, the organic salt and the nitrogen-containing small molecule are completely dissolved in the solvent, evaporated by heating, and then, without adding an additional template agent, the solid obtained by the heating and evaporation process is directly placed in a tubular furnace for high-temperature calcination, and finally, a simple acid solution etching process is performed to quickly and conveniently obtain the nitrogen-hybridized honeycomb carbon; in the second step, the nitrogen-hybridized honeycomb carbon and the gold are mixed. The cobalt precursor is mixed evenly in the solvent, and then the organic ligand is added to react. After the reaction, a metal organic framework / nitrogen-hybridized honeycomb carbon is obtained. In this step, the target metal organic framework / nitrogen-hybridized honeycomb carbon can be obtained by effectively regulating the reaction conditions of the metal cobalt precursor and the organic ligand; in the third step, the metal organic framework / nitrogen-hybridized honeycomb carbon, the metal nickel precursor and the metal iron precursor are mixed evenly in the solvent to obtain a mixed solution, and the nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material is prepared by precisely controlling the reaction conditions of the metal nickel precursor, the metal iron precursor and the metal organic framework / nitrogen-hybridized honeycomb carbon.

[0017] In addition, in the preparation method of the nitrogen-hybridized honeycomb carbon negative FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention, the template-free high-temperature carbonization strategy adopted is more convenient and faster than the traditional hard template method or soft template method, the process is simple, and the product treatment is relatively convenient and fast. It is suitable for the preparation of non-precious metals with high activity and high stability, such as Fe, Ni, Cu and other heterostructure catalysts.

[0018] Furthermore, the present invention uses non-precious metal precursors and organic small molecules as synthetic raw materials, the raw materials are abundant in reserves, the industrial cost is low, and it is suitable for medium-scale industrial production.

[0019] In addition, the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material prepared by the present invention has a typical honeycomb morphology and a scaly FeOOH / FeNiCo-LDH heterostructure, and can be used as a high-performance catalytic material with excellent performance and good stability. It has a relatively broad development prospect and application space in the catalytic conversion in the fields of energy and environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a scanning electron microscope image of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention;

[0021] Figure 2 is a transmission electron microscope image of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention;

[0022] Figure 3 is a selected area electron diffraction pattern of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention;

[0023] Figure 4 is an X-ray diffraction diagram of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention;

[0024] Figure 5 It is a performance test data diagram of the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following examples are combined with the accompanying drawings to describe a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, its preparation method and application

[0026] Give specific explanation.

[0027] <Example 1>

[0028] The preparation method of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material of this embodiment comprises the following steps:

[0029] Step 1, any one or more of sodium gluconate, sodium acetate, ammonium citrate, potassium citrate, sodium citrate and any one or more of aniline, alanine, glycine, urea, melamine, and hexamethylenetetramine are completely dissolved in deionized water, methanol, ethanol, ether, N, N-dimethylacetamide, and any one or more of N, N-dimethylformamide, and heated and evaporated in an oil bath, water bath, or sand bath at 50°C to 200°C; in an atmosphere of air, hydrogen, nitrogen, or argon, the heating rate is adjusted to 2°C / min to 20°C / min to raise the temperature to 400°C to 1200°C, and a high-temperature calcination process is performed for 0.5h to 8h, and an acid etching process is performed for 10min to 120min in a hydrochloric acid, sulfuric acid, or nitric acid solution with an etching temperature of 20°C to 100°C and an acid concentration of 0.1M to 2M to obtain nitrogen-hybridized honeycomb carbon. In this embodiment, the specific experimental process is as follows:

[0030] 7.90 g of sodium citrate and 0.91 g of urea were completely dissolved in 30 mL of deionized water, and the solvent was evaporated in an oil bath at 110 °C. The obtained white powder was placed in a tubular furnace with a heating rate of 5 °C / min and calcined at 800 °C in an argon atmosphere for 1 h. Then, it was etched with 0.1 M dilute hydrochloric acid, filtered, washed with water, and dried to obtain nitrogen-hybridized honeycomb carbon.

[0031] Step 2, 10 mg to 200 mg of nitrogen-hybridized honeycomb carbon and 1-5 mmol of any one or more of cobalt oxalate, cobalt sulfate heptahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt acetate tetrahydrate, and cobalt acetylacetonate are uniformly mixed in 10 mL to 200 mL of deionized water, methanol, ethanol, ether, N, N-dimethylacetamide, and any one or more of N, N-dimethylformamide, and then 0.5-50 mmol of any one or more of 2-aminoterephthalic acid, imidazole, 2-methylimidazole, and 2-ethylimidazole terephthalic acid are added to react, and a metal organic framework / nitrogen-hybridized honeycomb carbon is obtained after the reaction, and the molar ratio of the metal precursor to the organic ligand is 0.1 to 2.0. In this embodiment, the experimental process is as follows:

[0032] 294.0 mg of cobalt nitrate hexahydrate and 50 mg of nitrogen-hybridized honeycomb carbon obtained in step 1 were evenly dispersed in 20 mL of methanol solvent, and then 20 mL of methanol solution containing 335.1 mg of 2-methylimidazole was added. The mixed solution was stirred at room temperature for 6 hours, washed with methanol by centrifugation, and dried to obtain a metal organic framework / nitrogen-hybridized honeycomb carbon.

[0033] Step 3, 10 mg to 200 mg of metal organic framework / nitrogen-hybridized honeycomb carbon and 0.5 to 3.0 mmol of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel oxalate, nickel acetylacetonate, any one or more and 0.01 to 0.2 mmol of ferrous chloride tetrahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate, ferric acetate, anhydrous ferric chloride, ferric citrate, ferric acetate, ferric acetylacetonate, any one or more, in 10 mL to 200 mL of deionized water, methanol, ethanol ether, N, N-dimethylacetamide, N, N-dimethylformamide, any one or more, mix uniformly to obtain a mixed solution, transfer the mixed solution to a reactor, set the reaction temperature to 20 ° C to 300 ° C, set the heating rate to 1 ° C / min to 15 ° C / min, set the reaction time to 2h to 20h, react, and obtain a nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material. In this embodiment, the specific experimental process is as follows:

[0034] 50 mg of the metal organic framework / nitrogen-hybridized honeycomb carbon obtained in step 2, 445.1 mg of nickel nitrate hexahydrate and 10.0 mg of ferrous chloride tetrahydrate were evenly dispersed in 50 mL of ethanol solvent, and the mixed solution was transferred to a solvent thermal reactor. The heating rate was set to 5 ° C / min, the reaction temperature was 120 ° C, the reaction time was 8 h, and the mixture was washed with ethanol by centrifugation and dried to obtain the nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0035] Figure 1 is a scanning electron microscope image of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention, Figure 1 (a) is a scanning electron microscope image at a magnification of 20K, and (b) is a scanning electron microscope image at a magnification of 100K.

[0036] like Figure 1 As shown, the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material prepared in this example has a typical honeycomb morphology and a scaly FeOOH / FeNiCo-LDH heterostructure.

[0037] Figure 2 is a transmission electron microscope image of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention, Figure 2 (a) is a low-magnification transmission electron microscopy image, and (b) is a high-resolution transmission electron microscopy image.

[0038] like Figure 2As shown, the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material prepared in this example has an obvious heterogeneous interface and is evenly distributed on the nitrogen-hybridized honeycomb carbon in the form of flakes.

[0039] Figure 3 It is a selected area electron diffraction pattern of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention.

[0040] like Figure 3 As shown, the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material prepared in this embodiment has diffraction crystal forms of two phases, FeOOH and FeNiCo-LDH.

[0041] Figure 4 : is the X-ray diffraction diagram of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention.

[0042] like Figure 4 As shown, the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material prepared in this embodiment has three physical phase structures of graphite carbon, FeOOH and FeNiCo-LDH.

[0043] Figure 5 is a performance test data diagram of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material in Example 1 of the present invention, Figure 5 (a) is the performance test data of freshwater oxygen evolution reaction, (b) is the performance test data of seawater oxygen evolution reaction, (c) is the performance test data when applied to anion exchange membrane electrolyzer for electrolysis of fresh water, and (d) is the performance test data when applied to anion exchange membrane electrolyzer for electrolysis of seawater.

[0044] like Figure 5 As shown, the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material prepared in this embodiment has excellent freshwater oxygen evolution reaction performance and seawater oxygen evolution reaction performance, and can be further used as an anode electrocatalyst in an anion exchange membrane electrolyzer to electrolyze water to obtain relatively excellent water electrolysis performance.

[0045] Depend on Figure 1-5As shown, the preparation method of the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material provided by the present invention can successfully prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material having a typical honeycomb morphology and a scaly FeOOH / FeNiCo-LDH heterostructure, and the composite material has excellent catalytic activity and stability, and can be used as an electrocatalyst for efficient freshwater oxygen evolution reaction, seawater oxygen evolution reaction, and anion exchange membrane electrolyzer water electrolysis reaction.

[0046] <Example 2>

[0047] In this embodiment, based on the preparation conditions of Example 1, the sodium citrate in step 1 of Example 1 was replaced with potassium citrate, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0048] <Example 3>

[0049] In this embodiment, based on the preparation conditions of Example 1, urea in step 1 of Example 1 was replaced with melamine, and the other steps were the same as those of Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0050] <Example 4>

[0051] In this embodiment, based on the preparation conditions of Example 1, 0.91 g of urea in step 1 of Example 1 was replaced with 0.61 g of urea, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0052] <Example 5>

[0053] In this embodiment, based on the preparation conditions of Example 1, the argon gas in step 1 of Example 1 was replaced with nitrogen gas, and the other steps were the same as those of Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0054] <Example 6>

[0055] In this embodiment, based on the preparation conditions of Example 1, the dilute hydrochloric acid in step 1 of Example 1 was replaced with dilute sulfuric acid, and the other steps were the same as those of Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0056] <Example 7>

[0057] In this embodiment, based on the preparation conditions of Example 1, the cobalt nitrate hexahydrate in step 2 of Example 1 was replaced with cobalt acetate tetrahydrate, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0058] <Example 8>

[0059] In this embodiment, based on the preparation conditions of Example 1, 294.0 mg of cobalt nitrate hexahydrate in step 2 of Example 1 was replaced with 588.0 mg of cobalt nitrate hexahydrate, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0060] <Example 9>

[0061] In this embodiment, based on the preparation conditions of Example 1, 50 mg of nitrogen-hybridized honeycomb carbon in step 2 of Example 1 was replaced with 100 mg of nitrogen-hybridized honeycomb carbon, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0062] <Example 10>

[0063] In this embodiment, based on the preparation conditions of Example 1, the stirring reaction time of 6 hours in step 2 of Example 1 was replaced with 12 hours, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0064] <Example 11>

[0065] In this embodiment, based on the preparation conditions of Example 1, the 50 mg metal organic framework / nitrogen-hybridized honeycomb carbon in step three of Example 1 was replaced with 100 mg metal organic framework / nitrogen-hybridized honeycomb carbon, and the other steps were the same as in Example 1 to prepare a nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0066] <Example 12>

[0067] In this embodiment, based on the preparation conditions of Example 1, 10.0 mg of ferrous chloride tetrahydrate in step 3 of Example 1 was replaced with 15.0 mg of ferrous chloride tetrahydrate, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0068] <Example 13>

[0069] In this embodiment, based on the preparation conditions of Example 1, 50 mL of ethanol in step 3 of Example 1 was replaced with 80 mL of ethanol, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0070] <Example 14>

[0071] In this embodiment, based on the preparation conditions of Example 1, the reaction temperature of 120°C in step 3 of Example 1 was replaced by 150°C, and the other steps were the same as those of Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0072] <Example 15>

[0073] In this embodiment, based on the preparation conditions of Example 1, the reaction time of 8 h in step 3 of Example 1 was replaced by 10 h, and the other steps were the same as those of Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0074] <Example 16>

[0075] In this embodiment, based on the preparation conditions of Example 1, the heating rate of 5°C / min in step 3 of Example 1 was replaced by 8°C / min, and the other steps were the same as those in Example 1 to prepare a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

[0076] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, characterized in that: The following steps are involved: Step S1, completely dissolving the organic salt and the nitrogen-containing small molecules in a solvent, and performing heating evaporation, high-temperature calcination and acid etching processes to obtain nitrogen-hybridized honeycomb carbon; Step S2, mixing the nitrogen-hybridized honeycomb carbon and the metal cobalt precursor in a solvent, and then adding an organic ligand to react, so as to obtain a metal organic framework / nitrogen-hybridized honeycomb carbon; Step S3, mixing the metal organic framework / nitrogen-hybridized honeycomb carbon, metal nickel precursor and metal iron precursor in a solvent to obtain a mixed solution, transferring the mixed solution to a reactor to react under preset temperature control program conditions to obtain a nitrogen-hybridized honeycomb carbon loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material.

2. The method for preparing the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to claim 1, characterized in that: in, In step S1, the organic salt is any one or more of sodium gluconate, sodium acetate, ammonium citrate, potassium citrate, and sodium citrate. The nitrogen-containing small molecule is any one or more of aniline, alanine, glycine, urea, melamine, and hexamethylenetetramine. The solvent is any one or more of deionized water, methanol, ethanol, ether, N,N-dimethylacetamide, and N,N-dimethylformamide. The molar ratio of the organic salt to the nitrogen-containing small molecule is 0.1 to 5.

0.

3. The method for preparing the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to claim 1, characterized in that: in, In step S1, when the heating evaporation process is performed, the heating method is an oil bath, a water bath or a sand bath, and the heating temperature is 50° C. to 200° C. During the high-temperature calcination process, the solid obtained in the heating evaporation process is directly placed in a tube furnace for calcination without adding an additional template agent. The gas atmosphere is air, hydrogen, nitrogen or argon atmosphere, the temperature is 400°C to 1200°C, the heating rate is 2°C / min to 20°C / min, and the calcination time is 0.5h to 8h. When the acid etching process is performed, the acid solution used for etching is hydrochloric acid, sulfuric acid or nitric acid, the acid concentration is 0.1M-2M, the etching temperature is 20°C-100°C, and the etching time is 10min-120min.

4. The method for preparing the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to claim 1, characterized in that: in, In step S2, the reaction temperature is 20°C to 100°C, and the reaction time is 1h to 12h. The metal cobalt precursor is any one or more of cobalt oxalate, cobalt sulfate heptahydrate, cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt acetate tetrahydrate, and cobalt acetylacetonate. The organic ligand is any one or more of 2-aminoterephthalic acid, imidazole, 2-methylimidazole, and 2-ethylimidazole terephthalic acid. The solvent is any one or more of deionized water, methanol, ethanol, ether, N,N-dimethylacetamide, and N,N-dimethylformamide.

5. The method for preparing the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to claim 1, characterized in that: in, In step S2, the amount of nitrogen-hybridized honeycomb carbon is 10 mg to 200 mg. The amount of the metal precursor is 1-5 mmol, The amount of the organic ligand is 0.5-50 mmol, The molar ratio of the metal precursor to the organic ligand is 0.1 to 2.

0. The amount of the solvent used is 10 mL to 200 mL.

6. The method for preparing the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to claim 1, characterized in that: in, In step S3, the preset temperature control program conditions are set as follows: reaction temperature 20°C to 300°C, heating rate 1°C / min to 15°C / min, reaction time 2h to 20h, The metal nickel precursor is any one or more of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel oxalate, and nickel acetylacetonate. The metallic iron precursor is any one or more of ferrous chloride tetrahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate, ferric acetate, anhydrous ferric chloride, ferric citrate, ferric acetate, and ferric acetylacetonate. The solvent is any one or more of deionized water, methanol, ethanol ether, N,N-dimethylacetamide, and N,N-dimethylformamide.

7. The method for preparing the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to claim 1, characterized in that: in, In step S3, the amount of the metal organic framework / nitrogen hybridized honeycomb carbon is 10 mg to 200 mg. The amount of the solvent is 10 mL to 200 mL. The amount of the metal nickel precursor is 0.5 to 3.0 mmol. The amount of the metallic iron precursor is 0.01-0.2 mmol.

8. A nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material, characterized in that: The nanocomposite material is prepared by the method for preparing the nitrogen-hybridized honeycomb carbon-loaded FeOOH / FeNiCo-LDH heterostructure nanocomposite material according to any one of claims 1 to 7.

9. Use of the nitrogen-hybridized honeycomb carbon-supported FeOOH / FeNiCo-LDH heterostructure nanocomposite material as claimed in claim 8 as an electrocatalyst.

Citation Information

Patent Citations

  • Heteroatomized honeycomb carbon anchored cobalt / cobalt oxide heterostructure nano composite material and preparation method thereof

    CN116364950A

  • Nanometer flower-shaped FeOOH / NiFe-LDH composite material as well as preparation method and application thereof

    CN119287432A